2006
DOI: 10.1111/j.1365-2443.2006.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitotic function of Chk1 through phosphorylation at novel sites by cyclin‐dependent kinase 1 (Cdk1)

Abstract: Chk1 is phosphorylated at Ser317 and Ser345 by ATR in response to stalled replication and genotoxic stresses. This Chk1 activation is thought to play critical roles in the prevention of premature mitosis. However, the behavior of Chk1 in mitosis remains largely unknown. Here we reported that Chk1 was phosphorylated in mitosis. The reduction of this phosphorylation was observed at the metaphaseanaphase transition. Two-dimensional phosphopeptide mapping revealed that Chk1 phosphorylation sites in vivo were compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 32 publications
5
48
0
1
Order By: Relevance
“…Even higher levels were observed in a nocodazole-treated (ND) culture, where approximately 60% of cells were mitotic. Thus, Chk1 S301 phosphorylation increases as cells progress through the cell cycle with the highest levels observed in S and G2/M phase cells, consistent with the idea that it might be catalyzed by both Cdk1 and Cdk2 (Shiromizu et al, 2006;Ikegami et al, 2008).…”
Section: Cdk Phosphorylation Regulates Chk1 Activation N Xu Et Alsupporting
confidence: 81%
See 3 more Smart Citations
“…Even higher levels were observed in a nocodazole-treated (ND) culture, where approximately 60% of cells were mitotic. Thus, Chk1 S301 phosphorylation increases as cells progress through the cell cycle with the highest levels observed in S and G2/M phase cells, consistent with the idea that it might be catalyzed by both Cdk1 and Cdk2 (Shiromizu et al, 2006;Ikegami et al, 2008).…”
Section: Cdk Phosphorylation Regulates Chk1 Activation N Xu Et Alsupporting
confidence: 81%
“…Interestingly, it was recently reported that Chk1 itself is also a Cdk target (Shiromizu et al, 2006;Ikegami et al, 2008). During the G2/M transition, Cdk1 phosphorylates Chk1 at Ser286 and Ser301 to promote Chk1 transport from the nucleus to the cytoplasm during prophase and trigger a positive feedback loop that contributes to Cdk1 activation in the nucleus (Kramer et al, 2004;Enomoto et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If this point precedes the onset of mitosis in late G 2 , it is possible to predict a transition period during which Chk1 could no longer be activated in response to DNA damage but Chk2 would (Figure 8). In fact, there is evidence that Chk1 is refractory to ATR-mediated phosphorylation and activation by DNA damage in mitotic cells (Shiromizu et al, 2006), possibly owing to cell cycle phase-specific degradation of the adaptor protein Claspin (Mailand et al, 2006;Peschiaroli et al, 2006), therefore it is highly plausible that the transition precedes the onset of this phase. We hypothesize that during this transition period Chk2 becomes increasingly, and ultimately solely, responsible for G 2 delay in response to damage in cells which are imminently about to enter mitosis (Figure 8).…”
Section: Discussionmentioning
confidence: 99%